2021
DOI: 10.1080/21505594.2021.1924019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and evolution of the virulence plasmids encoding aerobactin and salmochelin in Klebsiella pneumoniae

Abstract: Virulence plasmids of hypervirulent Klebsiella pneumoniae (hvKp) have the potential to transfer to drug-resistant strains or integrate with other plasmids, facilitating the genome evolution of threatening pathogens. We conducted an in-depth analysis of the publicly available 156 complete genome sequences of hvKp together with a multi-region clinical cohort of 171 hvKp strains from China to provide evidence for the virulence plasmid evolution. Virulence plasmids were frequently detected in the ST23 and ST11 K. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…These virulence plasmids lacked virulence genes rmpA and iroBCDN when compared to typical virulence plasmid pLVPK, which may affect the virulence potentials of these CRKP strains. However, 96.2% of the virulence plasmids in the GenBank carried iucA , while only 46.8% carried iroB ( Tian et al, 2021 ). The virulence effects and any benefits of the iro deletion remains to be studied.…”
Section: Resultsmentioning
confidence: 99%
“…These virulence plasmids lacked virulence genes rmpA and iroBCDN when compared to typical virulence plasmid pLVPK, which may affect the virulence potentials of these CRKP strains. However, 96.2% of the virulence plasmids in the GenBank carried iucA , while only 46.8% carried iroB ( Tian et al, 2021 ). The virulence effects and any benefits of the iro deletion remains to be studied.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugative virulence plasmids were possibly formed by the insertion of an aerobactin cluster into an IncFIB K /IncFII conjugative plasmid (Tian et al, 2021), and the composition of pK2606 is concordant with this observation. There are also some other reports concerning conjugative virulence plasmids.…”
Section: A B Cmentioning
confidence: 53%
“…The most common virulence plasmids acquired by CRKP strains are non-conjugative pK2044-like plasmids, but their mechanism of transfer is still uncertain. Our previous study identified some conjugative virulence plasmids encoding aerobactin genes in Klebsiella pneumoniae (Tian et al, 2021). Considering their potential for self-conjugation, it is essential to confirm the virulence of the host bacteria and their ability to transfer to other strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations